Services of Specialist Doctor at Type C Regional General Hospital based on Regulation of the Minister of Health No. 3 of 2020 on Hospital Classification and License - Wahyudi; Irma Indra Wahyuni; Muhammad Firdan Resaldi; Mokhamad Khoirul Huda (Indian Journal of Forensic Medicine & Toxicology, 2021)
The problem occurs when the number of human resources for health workers, mainly the number of specialistdoctors, is not comparable to the number of hospitals in Indonesia, particularly in type C regional generalhospitals. Currently, many private hospitals are competing to provide better and quality services. When theyare sick, many people choose a hospital with a much better and modern service. It becomes a concern for thegovernment to meet its citizens’ basic needs in the health sector. The problem that lies behind the researchersto write is Regulation of the Minister of Health No.3 of 2020 on Hospital Classification and License to findout a legal review of specialist doctor services at type C regional general hospital. Based on the analysis ofthe Regulation of the MinisterNo. 3 of 2020 on hospital classification and license, the regulation does notregulate the minimum requirements for specialist doctors in each hospital classification. It causes an unequaldistribution of specialist doctors in type C regional general hospital and results in the unequal quality ofhealth services throughout Indonesia.